Strategi Fundraising dalam Meningkatkan Perolehan Dana Zakat, Infaq dan Sedekah (ZIS) di BAZNAS Kabupaten Jombang - Fitriyah, Norma Dwi; Rohman, Abdur (AL-Muqayyad, 2023)
BAZNAS Jombang is one of the institutions operating in the field social services have an important role in distributing aid to parties who need it by implementing various programs that aim to improve the social conditions of society. To achieve This goal BAZNAS Jombang requires financial resources, which in this case can be obtained by collecting funds or fundraising. Therefore, this research aims to find out more about the fundraising strategies used by BAZNAS Jombang. In this research, the researcher used the method descriptive qualitative to describe the fundraising strategy used by BAZNAS Jombang. The research results obtained are In conducting fundraising, BAZNAS Jombang uses 2 (two) The first strategy is a direct (offline) strategy such as direct mail, establishment of UPZ, collaboration with local government, pick-up service zakat, manuals, and organizing events. Meanwhile, the second strategy namely indirect (online) strategies such as social media campaigns and print, transfer and QRIS. This research is expected to provide a description and information regarding the fundraising strategy used by BAZNAS Jombang in increasing the acquisition of ZIS funds.